(untitled) (Modern Problems of Metallurgy, 2022)
Actual for modern engineering is the study of the influence of chemical composition and processing on the structure and mechanical properties during development of the new brands of the steel. The purpose of the study was the modeling of the role of the chemical composition for the formation of the mechanical properties and structure in determining the effect of the cooling rate on the austenitization temperatures of the 31CrMoV9 steel. It is known that the complex of mechanical properties of metal products depends on the number of alloying elements and the mode of heat treatment. Using the mathematical and physicochemical modeling for 31CrMoV9 steel were made dependent on the change in the mechanical properties of the alloy rolled products (σв, δ5) from the structural condition index (d). It is determined that for guaranteed compliance with the requirements of tensile strength (900-1000 MPa) and specific elongation (> 11%) the number of the alloying elements shall be corresponds to the following content: 2,46...2,62 % Сr, 0,2...0,24 % Mo and 0,17...0,19 % V. Received data are allow to forecast the rational mechanical properties of the heat treated rolled products depending on the change in the content of chromium, molybdenum and vanadium. Metallographic studies allowed to establish the influence of heat treatment parameters on the structure of the studied alloy steel. It is established that heating to the temperature А3+200°С and further continuous cooling with speeds > 0,8ºС/s prevents the formation of the pearlite structure, which during further heat treatment (annealing) promotes the passage of structural transformations (coagulation) in the steel. To prevent curvature of the metal, it is desirable to have cooling the rolled steel 31CrMoV9 at a speed of 0,8…2ºC/s. Recommended cooling rates allow to obtain a more acceptable structure for further processing with the required mechanical properties. Together with prognostication of the level of the mechanical properties for the certain chemical composition, these recommendations allow the rational use of the chemical elements and guaranteed compliance with the requirements of the European regulatory documentation EN10085:2001.